Exploring the Online Doctor-Patient Interaction on Patient Satisfaction Based on Text Mining and Empirical Analysis. Issue 5 (September 2020) - Chen, Shuqing; Guo, Xitong; Wu, Tianshi; Ju, Xiaofeng
Highlights: We combined a text mining and econometrics analysis technology to explore the mechanism of doctor-patient interaction in an online health community. Patient activeness as an antecedent factor could enhance the social support from a doctor, which indirectly affects patient satisfaction. Both the doctor's informational and emotional support plays a positive role for doctor-patient relationship. Patient disease severity plays an important role between doctor's social support and patient satisfaction. Abstract: In the online health community, the doctor-patient interaction is one of the most important functional modules. A large volume of unstructured text data has been generated in the doctor-patient interaction process. This development is worth exploring. In this paper, we mainly explore the influences of online doctor-patient interaction content on patient satisfaction. We collected the online doctor-patient interaction text data from a big online health community (http://haodf.com ) in China from January 2015 to December 2016, followed by the use of text mining and econometrics to test our hypotheses. The results indicate that the patient's activeness has a positive effect on a doctor's informational and emotional support. Furthermore, both a doctor's informational and emotional support are known to have a positive effect on patient satisfaction. More significantly, the effect of emotional support on patient satisfaction is more significant than that of informational support. In addition, the patient's disease severity strengthens the link between a doctor's informational and emotional support and that of patient satisfaction. This study has far-reaching significance for a better understanding of the doctor-patient interaction mechanism.